2003
DOI: 10.1074/jbc.m303894200
|View full text |Cite
|
Sign up to set email alerts
|

1,1′-Bis(anilino)-4-,4′-bis(naphtalene)-8,8′-disulfonate Acts as an Inhibitor of Lipoprotein Lipase and Competes for Binding with Apolipoprotein CII

Abstract: Lipoprotein lipase (LPL) is dependent on apolipoprotein CII (apoCII),and a slow off-rate with a dissociation rate constant k diss ‫؍‬ 1.2 ؋ 10 ؊4 s ؊1 . The high affinity binding of bis-ANS did not influence interaction of LPL with heparin or with lipid/water interfaces and did not dissociate the active LPL dimer into monomers. Analysis of fragments of LPL after photoincorporation of bis-ANS indicated that the high affinity binding site was located in the middle part of the N-terminal folding domain. We propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Nevertheless, as shown in Figure 4, a hypothetical model can be envisioned based on evidence gleaned from in vivo studies detailing the maturation of well-studied protein substrates, such as viral and some host proteins [72,106,107], and from in vitro studies monitoring the structure of folding intermediates occurring during the refolding of chemically denatured LPL [80,108,109]. In particular, LPL refolding experiments have demonstrated that folding of the smaller C-terminal domain happens quickly and completely, whereas folding of the N-terminal domain is much less efficient and occurs through folding intermediates exhibiting a degree of disordered tertiary structure [80].…”
Section: Mechanisms Of Lipase Maturationmentioning
confidence: 99%
“…Nevertheless, as shown in Figure 4, a hypothetical model can be envisioned based on evidence gleaned from in vivo studies detailing the maturation of well-studied protein substrates, such as viral and some host proteins [72,106,107], and from in vitro studies monitoring the structure of folding intermediates occurring during the refolding of chemically denatured LPL [80,108,109]. In particular, LPL refolding experiments have demonstrated that folding of the smaller C-terminal domain happens quickly and completely, whereas folding of the N-terminal domain is much less efficient and occurs through folding intermediates exhibiting a degree of disordered tertiary structure [80].…”
Section: Mechanisms Of Lipase Maturationmentioning
confidence: 99%
“…Previous work has shown that lipoprotein lipase (LPL) interacts strongly with, and in fact is inhibited by, the hydrophobic probe 4,4′‐dianilino‐1,1′‐binaphthyl‐5,5′‐disulfonic acid (bis‐ANS) [12]. Another hydrophobic probe, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…All measurements were made at 25°C. To obtain the dissociation constant ( K d ), fluorescence titration curves were analyzed using the equation: where F is the fluorescence intensity of the TF·bis‐ANS complex, [ TB ] is the concentration of the TF·bis‐ANS complex, k is a proportionality constant, [ T ] is the concentration of TF, and [ B ] is the concentration of free bis‐ANS at equilibrium (Lookene et al 2003). The data were also analyzed by Scatchard plot: where [ bound ] and [ free ] is the concentration of bound and free bis‐ANS at equilibrium, and n is the number of bis‐ANS molecules bound to TF.…”
Section: Methodsmentioning
confidence: 99%
“…The reactivation yield of GAPDH or lysozyme in the presence of TF without bis‐ANS were set as 100%. The parameter K i characterizing the inhibition efficiency was obtained from the equation: where A is the measured activity, A r is a calculated constant describing the activity of the TF‐bis‐ANS complex, K i is the inhibition constant, m is a proportionality constant, and C is the concentration of bis‐ANS (Lookene et al 2003).…”
Section: Methodsmentioning
confidence: 99%